2016
DOI: 10.1007/s11606-016-3780-5
|View full text |Cite
|
Sign up to set email alerts
|

Proposals to Conduct Randomized Controlled Trials Without Informed Consent: a Narrative Review

Abstract: BACKGROUND: Individual informed consent from all participants is required for most randomized clinical trials (RCTs). However, some exceptions-for example, emergency research-are widely accepted. METHODS: The literature on various approaches to randomization without consent (RWOC) has never been systematically reviewed. Our goal was to provide a survey and narrative synthesis of published proposals for RWOC. We focused on proposals to randomize at least some participants in a study without first obtaining cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Various studies have shown that at first glance, participants seem to favor an “ask each time” model in research . Those findings are inconsistent with the results of two studies exploring public attitudes toward consent in biobanking, both indicating that a broad one‐time opt‐in is preferred by the public in general .…”
Section: Resultsmentioning
confidence: 83%
“…Various studies have shown that at first glance, participants seem to favor an “ask each time” model in research . Those findings are inconsistent with the results of two studies exploring public attitudes toward consent in biobanking, both indicating that a broad one‐time opt‐in is preferred by the public in general .…”
Section: Resultsmentioning
confidence: 83%
“…In the worst scenario, the trial is terminated early 711. We should look for alternatives to the standard written informed consent for low risk pragmatic RCTs 2223…”
Section: Informed Consentmentioning
confidence: 99%
“…Based on the fact that patients are assigned to standard care interventions, no informed consent is sought either in low-risk pragmatic RCTs [ 17 ] or in prompted optional randomisation trials [ 18 , 19 ]. However, in a low-risk pragmatic RCT, patients do not have the possibility to choose one of the two standard treatments, whereas in a prompted optional randomisation trial, both the researchers and the enrolled patients can choose one type of treatment over another, despite the randomisation results [ 6 ].…”
Section: Informed Consent: When Is It Not Necessary?mentioning
confidence: 99%